Impact of a patient blood management program and an outpatient anemia management protocol on red cell transfusions in oncology inpatients and outpatients - Gross, I.; Gross, I.; Trentino, K.; Andreescu, A.; Pierson, R.; Maietta, R.; Farmer, Shannon; Farmer, S. (AlphaMed Press, 2016)
© AlphaMed Press 2016. Background. Patient blood management (PBM) programs are associated with reduced transfusion usage, reduced hospital costs, and improved patient outcomes.The application of PBM principles in patients with malignant disease might achieve similar results. However, this population presents unique challenges. The aim of the present study was to investigate the impact of a PBM program on blood usage and patient outcomes in cancer patients, particularly in the setting of restricted use of erythropoiesis-stimulating agents (ESAs). Materials and Methods. A retrospective observational study was performed of patients admitted with a primary diagnosis of malignancy treated at Eastern Maine Medical Center as inpatients or outpatients, or both, from January 2008 through July 2013. Results. The proportion of inpatients and outpatients receiving ESAs decreased from 2.9% in 2008 to 1.1% in 2013 (p <.001). During the same period, an increase occurred in the mean dose of intravenous (IV) iron from 447 mg (95% confidence interval [CI], 337-556) to 588 mg (95% CI, 458-718). The mean red blood cell (RBC) units transfused per inpatient and outpatient episode decreased from 0.067 to 0.038 unit (p <.001). In inpatients, significant increases occurred in the proportion of single-unit RBC transfusions (p <.001) and patients infused with IV iron (p =.02), and significant decreases in the mean pretransfusion hemoglobin (p =.02) and RBC transfusion rate (p =.04). In-hospital mortality and length of stay did not change significantly during this period. Conclusion. Despite the decreased use of ESA therapy, the implementation of a PBM program and outpatient anemia management protocol in cancer patients at our medical center was associated with significant reductions in RBC usage.